MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA SNADER GAME PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS 1 SDN 21 LIMBOTO - Yanawati A. Sutara; Lamsike Pateda; Dewi Darmiyani Napu (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the initial reading ability and how much the initial reading ability increases using the Snader Game media in the Indonesian Language subject of grade 1 students of SDN 21 Limboto. This type of research is classroom action research. The subjects of this study were grade 1 students, with a total of 26 students. Where male students consisted of 17 and female students were 9 students. The data analysis techniques used in this study were analysis of test results and analysis of observation results. Based on the results of the study conducted over two cycles, it shows an increase in reading ability from pre-cycle to cycle II. In the pre-cycle, the percentage of student completion was 67%, then increased to 73.8% in cycle I, and reached 85.7% in cycle II. This increase shows that the use of Snader Game media can help students more easily recognize letters, arrange letters into syllables, arrange words into syllables, and can read words in their entirety. In addition, the application of Snader Game media also makes the learning process more interesting and interactive so that students are more enthusiastic about participating in reading activities. Thus, it can be concluded that the application of the Snader Game media is effective in improving the initial reading skills of grade I students.